Very Early-Onset Inflammatory Bowel Disease (VEO-IBD) Presenting with Recurrent Leukocytoclastic Vasculitis Preceded by Streptococcal Pharyngitis - Ashley Fonseca; Julee Sunny; Lina M. Felipez (Case Reports in Pediatrics)
Inflammatory bowel disease (IBD) that presents in children <6 years of age is known as very early-onset IBD (VEO-IBD). Extraintestinal manifestations in IBD, such as erythema nodosum (EN), pyoderma gangrenosum (PG), and, less likely, leukocytoclastic vasculitis (LV), are more commonly present in Crohn’s disease. Association between LV and ulcerative colitis (UC) is not commonly seen. We report a case of a 6-year-old female with a VEO-IBD UC phenotype presenting with multiple episodes of leukocytoclastic vasculitis, each preceded by streptococcal pharyngitis. Prior to the diagnosis of VEO-IBD, a skin biopsy was obtained and had shown leukocytoclastic vasculitis with a negative IgA stain. Initial laboratory results were remarkable for leukocytosis and increased anti-strep O and anti-DNase B titers. Gastrointestinal panel PCR demonstrated Clostridium difficile toxin A/B. Treatment for LV consisted of methylprednisolone IV 20 mg for four days with a weaning schedule of prednisolone for two weeks and naproxen 250 mg BID for three days. Clostridium difficile was treated with metronidazole 250 mg TID for ten days. She remained stable for three years until she presented with continuous bloody stools, newly onset chest pain, and shortness of breath. Computed tomography angiogram (CTA) was normal. Stool calprotectin was elevated at 658 mcg/gm. Abdominal magnetic resonance enterography (MRE), esophagogastroduodenoscopy, and colonoscopy confirmed a VEO-IBD ulcerative colitis phenotype. She was started on infliximab 10 mg/kg every four weeks after infliximab titers, and antibodies were obtained. Currently, the patient remains on clinical and biochemical remission, with no recent LV episodes or recurrence of streptococcal pharyngitis. Our patient is unique as no case report has been published with multiple episodes of leukocytoclastic vasculitis in association with a VEO-IBD UC phenotype.